Creation of high-energy phonons by four-phonon processes in anisotropic phonon systems of He II - Adamenko, I.N.; Kitsenko, Yu.A.; Nemchenko, K.E.; Slipko, V.A.; Wyatt, A.F.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The problem of the creation of high-energy phonons (h-phonons) by a pulse of low-energy phonons (l-phonons) moving from a heater to a detector in superfluid helium, is solved. The rate of h-phonon creation is obtained and it is shown that created h-phonons occupy a much smaller solid angle in momentum space, than the l-phonons. An analytical expression for the creation rate of h-phonon, along the symmetry axis of a pulse, are de rived. It al lows us to get useful approximate analytical expressions for the creation rate of h-phonons. The time dependences of the parameters which de scribe the l-phonon pulse are obtained. This shows that half of the initial energy of l-phonon pulse can be transferred into h-phonons. The results of the calculations are com pared with experimental data and we show that this theory explains a number of experimental results. The value of the momentum, which separates the l- and h-phonon subsystems, is found.